IBM BANK SAMPAH DESA SEKARPURO KABUPATEN MALANG - Latifah, Sri Wahjuni (Studi Kasus Inovasi Ekonomi, 2016)
The population is fairly dense and home industryhad an impact on the level of the communityconsumption on the rise, and it willautomatically add the use of materials that posea litter. Actually, the existence of waste paperand plastics will be an interesting businessopportunity, generate and absorb labour ifmanaged with good management. One of thewaste management model is with the bank trash.However, it should be noted the bank trash bemanaged with a good administrative systems sothat depositors trust in such business.As it happens in Sekarpuro Village RW 09,Pakis, Malang. Actually, members of the PKKorganization, have a desire to manage wastewith the model bank trash. Because it has notbeen agreed by the forum, then these membersmove partially, and there has not management oflandfills also through bank trash management.The purpose of this activity is to establish theorganization managed bank trash with goodmanagement thus creating economic value addedcrap. While the benefits of these activities is toincrease awareness and knowledge of thecitizens about the problem of trash in itsenvironment as well as handling solutions. Themethod used through the socialization orextension to the community, the discussionidentified the type of waste, the establishment ofthe Organization the bank trash, administrativeand training programs development.